Lutra lutra - W. Christopher Wozencraft (Smithsonian Institution Press, 1993)
Lutra lutra (Linnaeus, 1758). Syst. Nat., 10th ed., 1:45. TYPE LOCALITY: "Europae aquis dulcibus, fluviis, flagnis, piscinis," subsequently restricted by Thomas (1911a) to " Upsala " (Sweden). DISTRIBUTION: Eurasia (excl. tundra and desert): Afghanistan, Albania, Algeria, Austria, Bangladesh, Belgium, Bulgaria, China, Czechoslovakia, Denmark, England, Estonia, Finland, France, Germany, Greece, Hungary, India, Indonesia, Iraq, Ireland, Israel, Italy, Japan, Jordan, Korea, Laos, Lithuania, Malaysia, Mongolia, Morocco, Norway, Pakistan, Poland, Portugal, Scotland, Spain, Sri Lanka, Sweden, Switzerland, Taiwan, Tunisia, Turkey, republics of the former USSR, Vietnam, and Yugoslavia. STATUS: CITES - Appendix I; IUCN - Vulnerable as L. I. lutra. SYNONYMS: amurensis Dybowski, 1922; angustifrons Lataste, 1885; aureventer Blyth, 1863; aurobrunneus Hodgson, 1839; baicalensis Dybowski, 1922; barang F. G. Cuvier, 1823; ceylonica Pohle, 1920; chinensis Gray, 1837; fluviatilis Leach, 1816; hanensis Matschie, 1907; indica Gray, 1837; intermedia Pohle, 1920; japonica Nehring, 1887; kamtschatica Dybowski, 1922; kutab Schinz, 1844; murinus Billberg, 1827; meridonalis Ognev, 1931; monticolus Hodgson, 1839; nair F. G. Cuvier, 1823; nepalensis Gray, 1865; nippon Imaizumi and Yoshiyuki, 1989; nudipes Melchior, 1834; oxiana Birula, 1915; piscatoria Kerr, 1792; roensis Ogilby, 1834; seistanica Birula, 1912; sinensis Trouessart, 1897; splendida Cabrera, 1906; stejnegeri Goldman, 1936; vulgaris Erxleben, 1777; whiteleyi Gray, 1867. COMMENTS: Imaizumi and Yoshiyuki (1989) considered Japanese otters a distinct species (L. nippon). Published as part of W. Christopher Wozencraft, 1993, Order Carnivora, pp. 279-348 in Mammal Species of the World (2 nd Edition), Washington and London :Smithsonian Institution Press on page 312, DOI: 10.5281/zenodo.7359191